Analysis of the Quality of Public Services in the Administrative Sector in Regency: Analisis Kualitas Pelayanan Publik Pada Bidang Administrasi di Kabupaten - Umaroh, Ria Syaidatul; Sukmana, Hendra (Indonesian Journal of Public Policy Review, 2023)
The purpose of this study is to analyze and describe the quality of public services in the field of administration in Sidoarjo Regency. In this research, there are problems regarding service quality, including village government officials who cannot master computers, village officials who are not disciplined in carrying out their duties. The method used in this research is a descriptive qualitative research method. Data collection techniques were carried out by interview, observation, and documentation with one key informant, namely the head of service in Medalem Village and seven supporting informants. The data analysis technique in this study uses the theory of Miles and Huberman which includes data collection, data reduction, data presentation, as well as drawing conclusions and verification. The results of the study indicate that administrative services are not complicated and the service process is not too long and is supported by adequate facilities and infrastructure. However, there are still Medalem Village government officials who often arrive late. In addition, there are still apparatuses who cannot master computers and there are those who do not master computers and the applications used in serving the community. Services in Medalem Village have not been supported by a place for complaints for the community which is useful for the government to know more about the shortcomings in its performance and what the needs of the community are.